2020
DOI: 10.1093/jas/skaa278.398
|View full text |Cite
|
Sign up to set email alerts
|

PSV-5 Dairy worker perspectives on performing euthanasia as an essential component of their job

Abstract: Euthanasia is a critical component of dairy management as it provides a way to alleviate animal suffering. Limited research explores dairy worker perspectives regarding their role in performing euthanasia or the impact of this practice on worker wellbeing. Additionally, training offered to caretakers is inconsistent in content and frequency and lacks cultural congruence. This project aimed to identify how euthanasia methods, procedures, and training affect caretaker attitudes towards performing on-farm euthana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Despite the fact that most workers indicated that euthanasia training was adequate, approximately one-third of respondents indicated that they would like to have more euthanasia training. Similarly, in other studies in swine and dairy caretakers, individuals have indicated a desire for more training with particular mention of in-person, on-the-job training [29,34,39,42]. In similar survey studies with livestock veterinarians, the participating veterinarians have indicated the desire to conduct more euthanasia training [4,6].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Despite the fact that most workers indicated that euthanasia training was adequate, approximately one-third of respondents indicated that they would like to have more euthanasia training. Similarly, in other studies in swine and dairy caretakers, individuals have indicated a desire for more training with particular mention of in-person, on-the-job training [29,34,39,42]. In similar survey studies with livestock veterinarians, the participating veterinarians have indicated the desire to conduct more euthanasia training [4,6].…”
Section: Discussionmentioning
confidence: 87%
“…euthanizing pigs" and 93% (42) agreed with the statement "I feel as though the euthanasia process on the farm is necessary".…”
Section: Attitudes Towards Performing On-farm Euthanasiamentioning
confidence: 99%
See 2 more Smart Citations